The effect of light pollution on orientation in Manx shearwaters (Puffinus puffinus) - Syposz, M (2020)
Humans introduce artificial light at night (ALAN) to the landscape for many reasons - to facilitate commuting to work, to improve their safety and to enhance the nocturnal aesthetics of places. The resulting change in light levels distorts a cue which living organisms use. A cue which, otherwise, has been predictable for billions of years. While some animals adjust to or even take advantage of ALAN, other species respond negatively, with populations suffering due to the presence of artificial light. In particular, burrow-nesting seabirds struggle with light pollution located near to their colony, with thousands of juvenile birds landing in lit-up areas during fledging season – termed ‘grounding’. The aim of this thesis is to investigate the behaviour of seabirds towards light pollution and, ultimately, to understand mechanistically the processes involved in grounding of seabirds. I explore, through observation and experimentation, the behavioural responses of an ALAN-susceptible seabird, the Manx shearwater (Puffinus puffinus) to artificial light. These experiments span the life-history stages of the Manx shearwater, from the orientation of juvenile shearwaters, before and during fledging, to the responses of breeding adults at the colony. I discover that the magnitude, but not direction, of behavioural reactions to artificial light is consistent across these life stages. At each life stage, reactions to ALAN appear to be related to the intensity and wavelength of light, the latter of which implies disruption of the visual system as a root cause of seabird grounding. Finally, in an applied study, I explore the effectiveness that updating old sodium pressure lamps with LEDs has had on shearwater grounding in a coastal town. Overall this thesis highlights the importance of understating the animals’ behaviour towards light pollution at different life stages and locations, contributing to the evidence base for mitigation measures that might be implemented in future.